Understanding the microscopic origin of the magnetic interactions in CoNb2O6 - Amanda A. Konieczna; David A. S. Kaib; Stephen M. Winter; Roser Valentí (npj Quantum Materials)
Abstract Motivated by the on-going discussion on the nature of magnetism in the quantum Ising chain CoNb2O6, we present a first-principles-based analysis of its exchange interactions with additional modeling, addressing drawbacks of a purely density functional theory ansatz. This method allows us to extract and understand the origin of the magnetic couplings—including all symmetry-allowed terms - and resolve conflicting model descriptions in CoNb2O6. We find that the twisted Kitaev chain and transverse-field ferromagnetic Ising chain views are mutually compatible, although additional off-diagonal exchanges are required for a complete picture. We show that the dominant exchange interaction is a ligand-centered process—involving e g electrons -, rendered anisotropic by low-symmetry crystal fields in CoNb2O6, resulting in dominant Ising exchange. Smaller bond-dependent anisotropies are found to originate from d − d kinetic exchange processes involving t 2g electrons. We demonstrate the validity of our low-energy model by comparing its predictions to measured THz and INS spectra.